Technology licensing or cost‐reducing outsourcing? Game theoretical analysis on consumers' home bias effects and firms' optimal strategies. (20th February 2020) - Chen, Tai‐Liang; Huang, Zuyi
Abstract: International cost‐reducing outsourcing lowers consumers' perceived quality of products due to home bias. This paper envisages a vertically differentiated Cournot duopoly associated with international, cost‐reducing outsourcing and non‐outsourcing schemes in both licensing and non‐licensing cases. It examines the impacts of home bias effect on the behaviour of firms and welfare. It shows that the optimal strategy of the patent holder varies from situation to situation associated with the home bias effect. In equilibrium, the dominant strategy for the patent holder is licencing and no outsourcing. If a licensee will outsource its inputs after upgrading the quality of its products, then the patent holder will earn higher profits than one in a case where the licensee does not outsource. If both the patent holder and the licensee produce without outsourcing, a welfare‐reducing licensing occurs. On the other hand, if the licensee outsources its production inputs but the patent holder does not outsource, then a welfare‐improving licensing generates a win‐win situation for the patent holder and for society. Furthermore, the smaller the quality gap between two goods prior to implementing licensing, the lower the royalty rate imposed by the patent holder.